Socio-cultural aspects of non-communicable disease prevention in three villages in the West Java - Erna Herawati; Yulia Sofiatin (Masyarakat, Kebudayaan dan Politik, 2021)
Community responses to disease, including non-communicable diseases, are influenced by the socio-cultural system. The system shapes community knowledge and belief on diseases, as well as community attitude and practice towards prevention and treatment. Drawing on the case in West Java Province, this study aims at identifying socio-cultural aspects in preventing non-communicable diseases. This study was conducted by using a qualitative design. The data were collected through in-depth interviews and archival study. This study found four socio-cultural aspects related to disease and the prevention and treatment of disease in West Java: 1) knowledge and practice of medicine covered in a local knowledge system about the prevention and treatment of non-communicable diseases, 2) local institutions, involving social institutions ranging from families, mosque neighborhood groups, and recitation groups, 3) social actors involved, such as ustaz, traditional leaders, and youth groups, 4) local health communication, using visual and audiovisual aids. This study concludes that these four aspects must be considered in designing a socio-cultural-based non-communicable disease prevention strategy, to be effective and in accordance with the socio-cultural context in West Java.